THE SYNOPSIS OF THE SECTION COMPACTOPRASON (AMARYLLIDACEAE, ALLIOIDEAE) IN UZBEKISTAN - Ergashov Ibrokhimjon Abduvali ugli; Yusupov Ziyoviddin Olimjon ugli; Safarov Fayzulla Panjiyevich (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The genus Allium, part of the Amaryllidaceae family, is well-known for its ecological, culinary, and medicinal importance, with key species such as Allium sativum (garlic) and Allium cepa (onion) playing vital roles in global agriculture and human health. This study examines the distribution and ecological characteristics of four Allium species (A. giganteum, A. majus, A. komarovii, and A. macleanii) across Central Asia, particularly in Uzbekistan. These species exhibit distinct environmental preferences, with A. giganteum showing broad adaptability to various altitudes and geographic regions, while species like A. majus and A. macleanii are more restricted in their distribution, highlighting their specialized habitat requirements. This research also focuses on the subgenus Melanocrommyum, particularly the Compactoprason section, which is characterized by unique floral structures and reproductive strategies, including large, densely packed inflorescences with over 3,000 flowers. The study utilizes field expeditions (2019–2024), herbarium specimens, and advanced mapping tools such as ArcGIS and Google Earth to analyze species distribution and temporal changes. Findings emphasize the need for targeted conservation efforts, especially for species with limited distribution ranges. This research contributes to a deeper understanding of the biodiversity of Allium species in Central Asia, particularly those in Uzbekistan, and underscores the ecological and taxonomic significance of the Compactoprason section within the broader subgenus Melanocrommyum.